Nineteen Eighty- Four : a novel - Smith, Winston; National Public Radio (U.S.) (Washington, D.C. : National Public Radio, 1983)
Compares facts of today's society with the fiction of George Orwell's classic novel. Also documents examples of police monitoring, subliminal messages, "new speak," fears of torture, social injustice, and moral decay.
A series or reports originally broadcast on the National Public Radio program All things considered.
Narrator, Winston Smith.
Keywords: Orwell, George, -- 1903-1950.